Gaming: essays on algorithmic culture - Galloway, Alexander R. (Electronic mediations ; 18, 2006)
Considers the video game as a distinct cultural form that demands a unique interpretive framework. This book analyzes video games as something to be played rather than as texts to be read, and traces how the "algorithmic culture" created by video games intersects with theories of visuality, realism, allegory, and the avant-garde.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé